Revisiting the establishment of the legal system in Dagestan in 1920–30s - N. T. Muslimova (Вестник Майкопского государственного технологического университета, 2024)
The Relevance of the research topic. Contradictory and diverse problems of the national-state structure in a federal state, involving consideration of national characteristics and cultural experience of the peoples included in it, make it relevant to study the historical experience of the formation of the Soviet legal system in Dagestan in 1920–30s.Problem statement. With the establishment of the Soviet power, the Dagestanis were offered a new model of social development. The transformation of the political, economic and social structure was accompanied by changes in the system of values, ideological attitudes, beliefs and norms that the majority of society had to share. Since the «outdated» value-normative system, regulating family, social, economic, and political relations, was focused on maintaining the existing development model, the approval of the new paradigm was difficult and contradictory.The Research objectives. To highlight the process of approval of the Soviet legal system in Dagestan in 1920-30s using reliable documentary material and accumulated historiographical experience.The Research methods. To solve the tasks set, the following methods were used: objectivism, historicism, historical-systemic and historical-typological.The Results and key conclusions. The legitimization of the Soviet legal system in the first years after the establishment of Soviet power required the preservation of the traditional elements of law for the Dagestanis – Muslim (Sharia) and customary (Adat) law. Since the late 1920s, the time of the «forced» construction of socialism in the country, the traditional legal structures in the Republic have been liquidated. Under the control of party bodies by the time of the adoption of the Constitution of 1937, the legal system of Dagestan acquires all-Russian structural and functional features. The establishment of a new legal system and a socialist sense of justice was promoted by the policy of indigenization (korenization) and promotion, which in Dagestan had its own specific features, due to the multinational nature of the republic.